Therapeutic dendritic cell cancer vaccines in hematologic malignancies. Issue 1 (5th May 2021) - Bindal, Poorva; Rosenblatt, Jacalyn; Avigan, David
Abstract: Tumor cells present antigen in the context of negative costimulation and immunosuppressive factors, resulting in the inhibition of T cell activation and immune tolerance. Dendritic cells (DCs) are a complex network of antigen presenting cells that play a critical role in maintaining the equilibrium between immune activation directed against pathogens and tolerance necessary to prevent damage mediated by autoreactive T cell clones. DCs uniquely induce primary immune responses through the constitutive and enhanced expression of positive costimulatory molecules and inflammatory cytokines necessary for T cell activation. In this context, the design of a cancer vaccine is based on the effective presentation tumor associated antigens to evoke an antigen specific activated T cell response, and importantly, immune memory. As such, DCs have played a major role in the development of cancer vaccine therapy as critical mediators of antigen presentation reversing a major component of tumor mediated immune suppression. DC based vaccines have involved the loading of individual tumor associated antigens or the use of whole tumor cells and have demonstrated potent induction of tumor specific immunity. The correlation of immune response with clinical outcome and integration of DC vaccines with other immune based therapy is currently being explored.